PENGARUH PEMBERIAN PUPUK KANDANG KOTORAN AYAM TERHADAP PERTUMBUHAN TANAMAN SAWI HIJAU (Brassica chinensis var. parachinensis) - Yovi Susanti; Maylani Lucky; Kristianus Heri Hartanto (Pusat Penelitian dan Pengabdian kepada Masyarakat, 2025)
Green mustard (Brassica chinensis var. parachinensis) is a horticultural vegetable plant whose leaves and young stems can be utilized. Mustard production still experiences winter, one of which is caused by low soil fertility. Efforts to increase soil fertility and mustard production can be done with organic fertilization. This study aims to determine the effect of chicken manure fertilizer on the growth of green mustard plants on alluvial soil. This study was conducted from February 21 to April 4, 2025 on Jalan Sintang, Gang Damai. This study used a completely randomized design (CRD) with one factor, namely S = Chicken Manure Fertilizer. The sample treatments are as follows S1: 20 g, S2: 60 g, S3: 100 g, S4: 140 g, S5: 180 g, the treatment was repeated 4 times and each treatment contained 4 plants so that the total sample was 80 plant samples measured. variables included: plant height, number of leaves, leaf width, fresh weight, plant weight without roots and root volume. The results showed that the provision of chicken manure fertilizer had a significant effect on all observation variables. The provision of Chicken Manure Fertilizer with a dose of 140 g / plant was better than other treatments, for the growth and yield of green mustard plants. Keywords : Mustard Greens, Chicken Manure Fertilizer, Alluvial